Developing A Sustainable Business Growth Strategy Through Franchising Case Study Of Company X - Haidhar Hibatullah Wurjanto; Yos Sunitiyoso; Hasnul Suhaimi (Eduvest - Journal of Universal Studies, 2024)
The primary objective of this research is to analyze the current business situation of Esteh Indonesia's Franchise Model, identify factors affecting its sustainability, and develop a new business strategy for sustainable growth. The conceptual framework is based on Rothaermel's AFI Framework, incorporating a comprehensive analysis of the 7P Marketing Mix, industry analysis using PESTEL and Porter’s Five Forces, and core competency evaluation through the VRIO framework. The literature review highlights key theoretical foundations, including franchising strategies, critical success factors, franchising relationship models, and the concept of Blitzscaling. The research method utilized a mixed-method approach, collecting qualitative data through one-on-one in-depth interviews with ten franchisees selected via convenience sampling revealed operational and market challenges and quantitative data through an online questionnaire administered to 200 customers. provided insights into purchasing behavior and brand perception. The qualitative data was analyzed using thematic content analysis to identify patterns and insights, while the quantitative data was analyzed using descriptive statistical analysis and Likert scales to measure customer perceptions and behaviors. To achieve sustainable growth, Esteh Indonesia should adopt a multifaceted strategy leveraging strengths, addressing weaknesses, capitalizing on opportunities, and mitigating threats. Focusing on a differentiation strategy based on the Porter’s Generic Strategy, emphasizing market penetration and product development based on the Ansoff Matrix , and utilizing the BCG Growth-Share Matrix to identify and replicate high-performing outlets, providing enhanced franchisee support, and upgrading to the 'Esteh 2.0' model will boost sales and brand equity, driving sustainable growth and solidifying Esteh Indonesia's market leadership.